Fundamentals of geotechnical engineering - Das, Braja M. (Cengage Learning, 2013)
Fundamentals of geotechnical engineering is a concise combination of the essential components of Braja Das' market leading texts, Principles of Geotechnical Engineering and Principles of Foundation Engineering. The text includes the fundamental concepts of soil mechanics as well as foundation engineering without becoming cluttered with excessive details and alternatives. FUNDAMENTALS features a wealth of worked out examples, as well as figures to help students with theory and problem solving skills. Das maintains the careful balance of current research and practical field applications that has made his books leaders in this area.